2017
DOI: 10.1186/s12950-017-0165-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic asthma and Mesenchymal stem cells: Hyaluronan and airway remodeling

Abstract: BackgroundPrevious studies have demonstrated that ovalbumin sensitization promotes chronic asthma phenotype in murine asthma model. Human mesenchymal stem cells (hMSCs) are multipotent cells in vitro that have been shown to decrease inflammation and can reverse airway remodeling when infused into an in vivo chronic asthma model. However, the mechanism by which hMSCs reverse remodeling is still unclear. In this study, we hypothesized that hMSCs influence remodeling by decreasing extracellular matrix (ECM) depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Systemic injection of human bone marrow MSCs via tail vein induced pulmonary macrophage polarization toward M2 type via the promotion of the TGF-β/Smad signaling pathway [116]. Interestingly, xenogeneic transplantation of human MSC retro-orbital administration in mice diminished the hyaluronan mucus in the chronic asthma model [32]. These findings support the assumption that autologous, allogeneic, and xenogeneic transplantation of MSCs could promote anti-inflammatory outcomes via engaging different mechanisms.…”
Section: Xenogeneic Transplantation Of Human Mscs Into An Animal Modementioning
confidence: 56%
“…Systemic injection of human bone marrow MSCs via tail vein induced pulmonary macrophage polarization toward M2 type via the promotion of the TGF-β/Smad signaling pathway [116]. Interestingly, xenogeneic transplantation of human MSC retro-orbital administration in mice diminished the hyaluronan mucus in the chronic asthma model [32]. These findings support the assumption that autologous, allogeneic, and xenogeneic transplantation of MSCs could promote anti-inflammatory outcomes via engaging different mechanisms.…”
Section: Xenogeneic Transplantation Of Human Mscs Into An Animal Modementioning
confidence: 56%
“…Of particular note is the potential role of aging in the parthenogenesis of asthma [28,29]. Many studies have demonstrated the exist of aging structural cells, immune cells and mesenchymal cells in asthmatic lung although the speci c role of aging cells in asthma is still not fully understood [20,30,31]. Meanwhile, some related studies have also con rmed the different expression of aging-related genes (such as TP53 and FOXO3) in the development of respiratory diseases [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Airway remodeling and inflammation in asthma are dependent on the ECM proteins, such as collagens and fibronectin (Liu et al, ). However, airway remodeling with excessive deposition of ECM is correlated with increased airway responsiveness and asthma severity (Goldstein, Lauer, Caplan, & Bonfield, ). In the present study, we found that casticin inhibited LPS‐induced expression of MUC5AC and deposition of ECM including collagen type I and fibronectin in 16‐HBE cells.…”
Section: Discussionmentioning
confidence: 99%
“…Airway remodeling and inflammation in asthma are dependent on the ECM proteins, such as collagens and fibronectin . However, airway remodeling with excessive deposition of ECM is correlated with increased airway responsiveness and asthma severity (Goldstein, Lauer, Caplan, & Bonfield, 2017).…”
Section: Discussionmentioning
confidence: 99%